Clarification of rules of acceptance in making business contracts - Jalil, Md Abdul (Canadian Center of Science and Education, 2011)
Business firms and Business corporations enter into thousands of contracts everyday. Making a formal and written contract is very important for business corporations and firms although oral contracts are accepted and recognized by law. There are certain rules on making a valid formal contract. If the business firms do not have knowledge of those contract formation rules and they make contracts in ignorance of those rules, their contracts would be liable to be declared as null and void by the court of law if it is referred to it to determine its validity or to get a remedy for breach of contracts by one of the parties in the contract. In this paper I have not discussed all the elements of a valid contract. I have discussed only one of the fundamental elements of a valid contract that is ‘acceptance’. In a business contract, there must have be an ‘offer’ and an ‘acceptance’, to make a valid contract, if not the contract will not be valid, recognized and enforceable in the court of law. The objective of this paper is to clarify the rules of making a valid ‘acceptance’ which may lead to making a binding contract between the parties.